A Five-Year strategic financial plan for Duty Free Philippines - Bernal, Lynskey., Eusebio, Camille P., Magpoot, Gelyn D., Regala, Mark Jericho B., Yu, Ma. Christina Ellor M. 4 0 16; 5
ABSTRACT: The study provides a comprehensive five-year strategic financial plan for Duty Free Philippines Corporation (DFPC), aiming to address the corporation's financial challenges and ensure its long-term stability. DFPC, as a government-owned and controlled corporation (GOCC), holds a pivotal role in supporting the Philippine tourism industry by offering duty- and tax-free goods to international travelers. While DFPC has demonstrated substantial growth and market presence in recent years, the corporation has encountered significant financial setbacks, particularly exacerbated by the COVID-19 pandemic, which resulted in notable revenue losses. The strategic plan identifies key internal strengths of DFPC, including its exclusive market access, innovative marketing approaches, and ongoing operational expansion. These strengths are bolstered by external opportunities such as the recovery of global tourism, advancements in digital platforms, and increasing consumer demand for tax-free shopping. However, the analysis also uncovers critical internal weaknesses, such as financial instability, supply chain inefficiencies, and employee morale concerns, compounded by external threats like heightened competition, macroeconomic uncertainties, and rapid technological advancements reshaping the retail landscape. In conclusion, the study underscores the critical importance of resilience and adaptability in navigating the challenges of an evolving market. By leveraging its strengths and addressing its vulnerabilities, DFPC is well-positioned to reclaim its leadership in the duty-free retail industry and contribute to the revitalization of Philippine tourism. The proposed financial plan serves as a roadmap for sustainable growth, aiming to ensure DFPC remains a key player in promoting the country as a premier travel destination. Keywords: Strategic financial planning, Duty Free Philippines Corporation, tourism-driven retail, financial instability, COVID-19 impact, competitiveness.
Financial Plan: (BSBA major in Financial Management) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2